Enterovirus D68 – The New Polio? - Cassidy, Hayley; Poelman, Randy; Knoester, Marjolein; Van Leer-Buter, Coretta C.; Niesters, Hubert G. M. (Frontiers in Microbiology, 2018)
Enterovirus D68 (EV-D68) has emerged over the recent years, with large outbreaks worldwide. Increased occurrence has coincided with improved clinical awareness and surveillance of non-polio enteroviruses. Studies showing its neurotropic nature and the change in pathogenicity have established EV-D68 as a probable cause of Acute Flaccid Myelitis (AFM). The EV-D68 storyline shows many similarities with poliovirus a century ago, stimulating discussion whether EV-D68 could be ascertaining itself as the “new polio”. Increasing awareness amongst clinicians, incorporating proper diagnostics and integrating EV-D68 into accessible surveillance systems in a way that promotes data sharing, will be essential to reveal the burden of disease. This will be a necessary step in preventing EV-D68 from becoming a threat to public health.